(untitled) (Discourse of Law and Administration, 2023)
The PSPP decision of the German Federal Constitutional Court has triggered strong reactions and even an infringement procedure against Germany, which has been terminated in the meantime. In the debate on the preservation – or re-establishment – of Union law standards of the rule of law, it has even been interpreted as evidence of the justification of a fundamental critique, especially by the Polish government, of the role of the European institutions in their relationship to the member states. In contrast, this article formulates the thesis that such an instrumentalisation of the decision turns the content of the judgment of 5 May 2020 into its opposite. Against the background of a concise overview of the core statements of German constitutional law on Germany’s relationship with the European Union, one of the main objectives of the decision is to strengthen – not weaken – the Court of Justice of the European Union; the criticism of the Federal Constitutional Court is not directed against an excessive, but on the contrary against an insufficient exercise of the control mandate incumbent on the ECJ. With a view to the combination of conceptual diversity and openness on the one hand and the necessity of strictly maintaining „red lines” on the other, which is characteristic of the principle of the rule of law under European Union law, the question arises whether the debate about „the final say” in the European „Dialogue des Juges” may ultimately leave the creative potential of the conflict about the relationship between the supreme courts of the Member States and the European supreme courts unexploited.